Surface-decorated macadamia (Macadamia sp.) nutshells for the detoxification of chromium(VI) polluted water. - Moyo, Malvin (Vaal University of Technology, 2021)
Driven by the need for sustainably sourced catalysts and the use of reaction systems that generate environmentally benign by-products, the present study aimed to deposit stable, dispersed palladium (Pd) nanoparticles on the modified surfaces of granular macadamia nutshell (MNS) biomass for catalytic reduction of hexavalent chromium [Cr(VI)] to trivalent chromium [Cr(III)]. Through wet impregnation with Pd(II) ions and subsequent hydrazinemediated reduction to Pd(0), Pd nanoparticles were embedded in a scaffold of polyethyleneimine grafted on bleached MNS previously coated with a chemically bound layer of polyglycidyl methacrylate. Visualization and imagery from scanning electron microscopy showed the formation of different layers of the polymeric coating and dispersed palladium resulting from surface modification and palladium nanoparticle synthesis, respectively. X-ray diffraction, energy-dispersive X-ray spectroscopic, and X-ray photoelectron spectroscopic analysis confirmed the formation of Pd on the modified MNS surface. An estimate of 5.0 nm for crystallite size was calculated by application of the Scherrer equation. The composite material, denoted Pd@PEI-MNS, exhibited catalytic activity in formic acidmediated Cr(VI) reduction. Through a one-factor-at-a-time experimental design, the activity of the Pd@PEI-MNS was illustrated to be dependent on solution pH; initial Cr(VI) concentration, initial formic acid concentration, and presence of competing anions; Pd@PEI-MNS dose; and temperature. Subsequent modeling of the Cr(VI) removal process by response surface methodology revealed that the most influential factor was Pd@PEI-MNS dose followed by temperature and formic acid concentration. The influence of initial Cr(VI) concentration, was surpassed by the dose-temperature and dose-formic acid concentration interactive effects. Elucidation of the Cr(VI) removal mechanism by XPS and FTIR demonstrated the active participation of surface –CH2OH functional groups, the bulk of which originated from the reduction of esters of the grafted ligands. Replacement of formic acid with hydrochloric acid in the reaction medium limited the Cr(VI) removal process to adsorption with non-extensive redox reaction with –CH2OH groups. Where the redox reactions converted formic acid to carbon dioxide, the –CH2OH groups were converted to –COO– groups.
Ph. D. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Macadamia nutshells; Detoxification of chromium; Polluted water; Dissertations, Academic -- South Africa.; Nanostructured materials.; Water -- Purification -- Chromium removal.; Water -- Pollution.